Functional structure and method for producing the functional structure
Patent Information
- Application Number
- JP2023061152
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-05-31
- Filing Date
- 2023-04-05
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2038-05-31
AI Technical Summary
【0013】 本発明によれば、機能性物質の機能低下を抑制して長寿命化を実現することができ、煩雑な交換作業を要せず、省資源化を図ることができる機能性構造体を提供することができる。
Smart Images

Figure 0007635943000019 
Figure 0007635943000020 
Figure 0007635943000021
Abstract
Description
[Technical field]
[0001] The present invention relates to a functional structure having a skeleton with a porous structure and a functional substance, and a method for producing the functional structure. [Background technology]
[0002] In the refineries of petroleum complexes, a petrochemical raw material called naphtha and various fuels such as heavy oil, diesel, kerosene, gasoline, and LPG are produced from crude oil. Because crude oil is a mixture of the above petrochemical raw materials, various fuels, and various impurities, a process is required to distill and separate the various components contained in the crude oil.
[0003] In the oil refining process, the difference in boiling points of each component is utilized, and the crude oil is heated on the trays in the tower of the atmospheric distillation unit to separate each component, and each separated substance is concentrated. As a result, low boiling point substances such as LPG and naphtha are extracted on the upper trays of the atmospheric distillation unit, while high boiling point substances such as heavy oil are extracted from the bottom of the atmospheric distillation unit. Various fuel products are then produced by subjecting the separated and concentrated substances to secondary treatment such as desulfurization.
[0004] In general, oil reforming catalysts are used in the above-mentioned oil refining process to efficiently reform low-boiling naphtha, etc., to produce high-octane gasoline, etc. The naphtha fraction in crude oil has a low octane number as is and is unsuitable for use as gasoline to run vehicles, so the paraffin and naphthene components with low octane numbers in the naphtha fraction are reformed into aromatic components with high octane numbers using an oil reforming catalyst, thereby producing reformed gasoline with properties suitable for use as a vehicle fuel.
[0005] In addition, with the heavier crude oil, hydrocracking is being carried out to further decompose the desulfurized heavy oil and desulfurized heavy light oil obtained by hydrodesulfurizing heavy oil in a hydrodesulfurization unit such as a direct desulfurization unit or an intermediate desulfurization unit, thereby increasing the production of desulfurized naphtha, desulfurized kerosene, desulfurized light oil, etc. For example, by hydrocracking atmospheric distillation residual oil, the yield of desulfurized light oil fraction and desulfurized naphtha fraction is increased to reduce the desulfurized heavy oil, and the desulfurized heavy oil is produced in a catalytic cracking unit to produce an LPG fraction, an FCC gasoline fraction, and an LCO fraction, thereby reducing the residual oil and increasing the light oil fraction. At this time, catalysts made of a crystalline aluminosilicate carrier, which is a typical zeolite, and hydrocracking catalysts containing zeolite and porous inorganic oxide in a specific ratio have been proposed.
[0006] For example, a hydrocracking catalyst has been disclosed in which a metal selected from Pd, Pt, Co, Fe, Cr, Mo, W, and mixtures thereof is deposited on the surface of a carrier made of Y-type zeolite (Patent Document 1).
[0007] In the field of automobiles, a ceramic catalyst body has been proposed as a catalytic structure for exhaust gas from vehicles equipped with diesel engines, in which a ceramic carrier is disposed on the surface of a substrate ceramic and both a main catalyst component and a promoter catalyst component are supported on the ceramic carrier. In this ceramic catalyst body, a large number of pores consisting of lattice defects in the crystal lattice are formed on the surface of the ceramic carrier made of γ-alumina, and the main catalyst components consisting of Ce-Zr, Pt, etc. are directly supported near the surface of the ceramic carrier (Patent Document 2). [Prior art documents] [Patent documents]
[0008] [Patent Document 1] US Patent Application Publication No. 2016 / 0030934 [Patent Document 2] US Patent Application Publication No. 2003 / 0109383 Summary of the Invention [Problem to be solved by the invention]
[0009] However, in the above-mentioned catalyst structure, since the catalyst particles are supported on the surface or near the surface of the carrier, the catalyst particles move within the carrier due to the influence of the force and heat received from the fluid such as the reformed substance during the reforming process, and the catalyst particles are likely to aggregate (sinter) with each other. When the catalyst particles aggregate with each other, the effective surface area as a catalyst decreases, and the catalytic activity decreases, so that the life becomes shorter than usual. Therefore, the catalyst structure itself must be replaced or regenerated in a short period of time, and there is a problem that the replacement work is complicated and resource saving cannot be achieved. In addition, since the catalyst for oil reforming is usually connected to the downstream side of the atmospheric distillation unit and used continuously in the oil refining process, it is difficult to apply the catalyst reactivation technology, and even if the reactivation technology can be applied, the work is very complicated. In addition, suppression or prevention of such deterioration of function over time is cited as an issue not only in the field of catalysts but also in various technical fields, and a solution is desired to maintain the function for a long time.
[0010] The object of the present invention is to provide a functional structure and a method for manufacturing a functional structure that can suppress functional deterioration of functional materials to achieve a long life, do not require complicated replacement work, and can save resources. [Means for solving the problem]
[0011] As a result of intensive research into achieving the above-mentioned object, the inventors have found that a functional structure can be obtained which comprises a porous skeleton composed of a zeolite-type compound and at least one functional substance contained within the skeleton, the skeleton having passages which communicate with each other, and the functional substance being present in at least the passages of the skeleton, thereby suppressing functional deterioration of the functional substance and realizing a longer life, and have completed the present invention based on this finding.
[0012] That is, the gist of the present invention is as follows. [1] A porous framework composed of a zeolite-type compound; At least one functional substance present within the scaffold; Equipped with The framework has passages communicating with each other, A functional structure, characterized in that the functional substance is present in at least the passages of the framework, and the average particle size of the functional substance is less than 30 nm. [2] The functional structure according to [1] above, characterized in that the average particle size of the functional substance is less than 5.0 nm. [3] The functional structure according to [2] above, wherein the average particle size of the functional substance is less than 2.0 nm. [4] The passage has one of one-dimensional pores, two-dimensional pores, and three-dimensional pores defined by the framework structure of the zeolite-type compound, and an enlarged portion different from any of the one-dimensional pores, the two-dimensional pores, and the three-dimensional pores; and The functional structure according to any one of the above [1] to [3], characterized in that the functional substance is present at least in the expanded diameter portion. [5] The functional structure according to [4] above, wherein the enlarged diameter portion connects a plurality of holes constituting any one of the one-dimensional hole, the two-dimensional hole, and the three-dimensional hole. [6] The functional material is a catalytic material; The functional structure according to any one of the above [1] to [5], wherein the framework is a support that supports the at least one catalytic substance. [7] The functional structure according to [5] above, wherein the catalytic substance is metal oxide fine particles. [8] The functional structure according to [6] above, characterized in that the average particle size of the metal oxide microparticles is larger than the average inner diameter of the passages and is equal to or smaller than the inner diameter of the expanded portion. [9] The functional structure according to the above [7] or [8], characterized in that the metal element (M) of the metal oxide fine particles is contained in an amount of 0.5 to 2.5 mass % relative to the functional structure.
[10] The functional structure according to any one of the above [6] to [9], wherein the ratio of the average particle diameter of the metal oxide microparticles to the average inner diameter of the passages is 0.06 to 500.
[11] The functional structure according to the above
[10] , wherein a ratio of an average particle size of the metal oxide fine particles to an average inner diameter of the passages is 0.1 to 45.
[12] The functional structure according to the above
[11] , wherein the ratio of the average particle diameter of the metal oxide fine particles to the average inner diameter of the passages is 1.3 to 3.5.
[13] The average inner diameter of the passages is 0.1 nm to 1.5 nm; The functional structure according to any one of the above [4] to
[12] , wherein the inner diameter of the expanded portion is 0.5 nm to 50 nm.
[14] The functional structure according to any one of the above [1] to
[13] , further comprising at least one functional substance held on the outer surface of the framework.
[15] The functional structure according to
[14] above, characterized in that the content of the at least one functional substance contained within the framework is greater than the content of the at least one functional substance held on the outer surface of the framework.
[16] The functional structure according to any one of the above [1] to
[15] , wherein the zeolite type compound is a silicate compound.
[17] An impregnation step of adding a surfactant to a precursor material (A) for obtaining a porous structure framework composed of a zeolite-type compound, and then impregnating the precursor material with a metal-containing solution to obtain a precursor material (B); A calcination step of calcining the precursor material (B) to obtain a precursor material (C); an addition step of adding a structure-directing agent that defines the skeletal structure of the skeleton to the precursor material (C); a hydrothermal treatment step of hydrothermally treating the precursor material (C) to which the structure-directing agent has been added; A method for producing a functional structure, comprising:
[18] The method for producing a functional structure according to the above
[17] , wherein the molar ratio of silicon in the precursor material (A) to the surfactant is 25 or less.
[19] The method for producing a functional structure according to the above
[18] , wherein the molar ratio of silicon in the precursor material (A) to the surfactant is 5 or less.
[20] The method for producing a functional structure according to any one of the above
[17] to
[19] , characterized in that in the impregnation step, the metal-containing solution is added to the precursor material (A) in multiple batches, thereby impregnating the precursor material (A) with the metal-containing solution.
[21] The method for producing a functional structure according to any one of the above items
[17] to
[20] , characterized in that when the precursor material (A) is impregnated with the metal-containing solution in the impregnation step, an amount of the metal-containing solution added to the precursor material (A) is adjusted so that a ratio of silicon (Si) constituting the precursor material (A) to a metal element (M) contained in the metal-containing solution added to the precursor material (A) (atomic number ratio Si / M) is 10 to 1000.
[22] The method for producing a functional structure according to the above
[17] , wherein the hydrothermal treatment step is carried out in a basic atmosphere. Effect of the Invention
[0013] According to the present invention, it is possible to provide a functional structure that can suppress the functional deterioration of a functional substance, thereby realizing a longer life, does not require complicated replacement work, and can achieve resource conservation. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a schematic diagram showing the internal structure of a functional structure according to an embodiment of the present invention, with FIG. 1(a) being an oblique view (partially shown in cross section) and FIG. 1(b) being a partially enlarged cross-sectional view. [Diagram 2] 2A and 2B are partially enlarged cross-sectional views for explaining an example of the function of the functional structure of FIG. 1, where FIG. 2A illustrates the sieving function and FIG. 2B illustrates the catalytic function. [Diagram 3] FIG. 3 is a flowchart showing an example of a method for manufacturing the functional structure of FIG. [Figure 4] FIG. 4 is a schematic diagram showing a modified example of the functional structure of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings.
[0016] [Configuration of functional structures] Fig. 1 is a diagram showing a schematic configuration of a functional structure according to an embodiment of the present invention, where (a) is a perspective view (partially shown in cross section), and (b) is a partially enlarged cross-sectional view. Note that the functional structure in Fig. 1 shows one example, and the shape, dimensions, etc. of each component according to the present invention are not limited to those in Fig. 1.
[0017] As shown in FIG. 1( a ), the functional structure 1 comprises a porous framework 10 made of a zeolite-type compound, and at least one functional substance 20 present within the framework 10 .
[0018] The functional material 20 is a material that exerts one or more functions, either alone or in cooperation with the framework 10. Specific examples of the functions include a catalytic function, a light emitting (or fluorescent) function, a light absorbing function, and a recognition function. The functional material 20 is preferably a catalytic material having a catalytic function. When the functional material 20 is a catalytic material, the framework 10 is a carrier that supports the catalytic material.
[0019] In the functional structure 1, a plurality of functional substances 20, 20, ... are encapsulated in a highly dispersed state inside the porous structure of the framework 10. A catalyst substance, which is an example of the functional substance 20, is preferably at least one of metal oxide fine particles and metal fine particles. The metal oxide fine particles and metal fine particles will be described in detail later. The functional substance 20 may also be particles containing a metal oxide or metal alloy, or a composite material thereof.
[0020] 1(b), the skeleton 10 has a porous structure, and preferably has a plurality of pores 11a, 11a, ..., thereby providing interconnected passages 11. The functional substance 20 is present in at least the passages 11 of the skeleton 10, and is preferably retained in at least the passages 11 of the skeleton 10.
[0021] With this configuration, the movement of the functional material 20 within the framework 10 is restricted, and the aggregation of the functional materials 20, 20 is effectively prevented, so that the highly dispersed state of the functional material 20 is maintained for a long period of time. As a result, the reduction in the effective surface area of the functional material 20 can be effectively suppressed, and the function of the functional material 20 is maintained for a long period of time. That is, according to the functional structure 1, the deterioration of the function due to aggregation of the functional material 20 can be suppressed, and the life of the functional structure 1 can be extended. Furthermore, the extended life of the functional structure 1 can reduce the frequency of replacement of the functional structure 1, and the amount of waste of used functional structures 1 can be significantly reduced, thereby saving resources.
[0022] Usually, when a functional structure is used in a fluid (e.g., heavy oil or reformed gas such as NOx), it may be subjected to an external force from the fluid. In this case, if the functional substance is merely held in an attached state on the outer surface of the skeleton 10, there is a problem that the functional substance is easily detached from the outer surface of the skeleton 10 due to the influence of the external force from the fluid. In contrast, in the functional structure 1, the functional substance 20 is held at least in the passage 11 of the skeleton 10, so that the functional substance 20 is unlikely to be detached from the skeleton 10 even if it is affected by the external force of the fluid. That is, when the functional structure 1 is in a fluid, the fluid flows into the passage 11 from the hole 11a of the skeleton 10, so that the speed of the fluid flowing in the passage 11 is considered to be slower than the speed of the fluid flowing on the outer surface of the skeleton 10 due to the flow path resistance (friction force). Due to the influence of such flow path resistance, the pressure that the functional substance 20 held in the passage 11 receives from the fluid is lower than the pressure that the functional substance receives from the fluid outside the skeleton 10. Therefore, it is possible to effectively prevent the functional substance 20 contained in the skeleton 11 from being released, and to stably maintain the function of the functional substance 20 for a long period of time. Note that it is considered that the above-mentioned flow path resistance becomes larger as the passage 11 of the skeleton 10 has a plurality of bends and branches and the interior of the skeleton 10 has a more complex, three-dimensional structure.
[0023] Moreover, the passage 11 preferably has one of one-dimensional, two-dimensional and three-dimensional pores defined by the framework structure of the zeolite-type compound, and an expanded diameter portion 12 different from any of the one-dimensional, two-dimensional and three-dimensional pores. In this case, the functional substance 20 is preferably present at least in the expanded diameter portion 12, and more preferably is included in at least the expanded diameter portion 12. The one-dimensional pore here refers to a tunnel-type or cage-type pore forming a one-dimensional channel, or a plurality of tunnel-type or cage-type pores (a plurality of one-dimensional channels) forming a plurality of one-dimensional channels. The two-dimensional pore refers to a two-dimensional channel in which a plurality of one-dimensional channels are two-dimensionally connected, and the three-dimensional pore refers to a three-dimensional channel in which a plurality of one-dimensional channels are three-dimensionally connected. This further restricts the movement of the functional substance 20 within the framework 10, and makes it possible to more effectively prevent the functional substance 20 from being separated or the functional substances 20, 20 from aggregating together. Inclusion refers to a state in which the functional substance 20 is encapsulated in the framework 10. In this case, the functional substance 20 and the framework 10 do not necessarily need to be in direct contact with each other, and the functional substance 20 may be indirectly held in the framework 10 with another substance (e.g., a surfactant, etc.) intervening between the functional substance 20 and the framework 10.
[0024] 1(b) shows a case where the functional substance 20 is encapsulated in the enlarged diameter portion 12, but the present invention is not limited to this configuration, and the functional substance 20 may be present in the passage 11 with a part of it protruding outside the enlarged diameter portion 12. The functional substance 20 may also be partially embedded in a part of the passage 11 other than the enlarged diameter portion 12 (for example, an inner wall part of the passage 11) or held by adhesion or the like. In addition, it is preferable that the expanded diameter portion 12 communicates with the plurality of holes 11a, 11a constituting any one of the one-dimensional holes, the two-dimensional holes, and the three-dimensional holes, so that a separate passage different from the one-dimensional holes, the two-dimensional holes, or the three-dimensional holes is provided inside the framework 10, thereby enabling the function of the functional substance 20 to be more effectively exhibited.
[0025] Moreover, the passage 11 is formed three-dimensionally inside the framework 10 including a branching portion or a junction portion, and the enlarged diameter portion 12 is preferably provided at the branching portion or the junction portion of the passage 11 .
[0026] The average inner diameter D of the passage 11 formed in the skeleton 10 F is calculated from the average value of the minor axis and major axis of the pores 11a constituting any one of the one-dimensional pores, the two-dimensional pores, and the three-dimensional pores, and is, for example, 0.1 nm to 1.5 nm, and preferably 0.5 nm to 0.8 nm. E The inner diameter D of the expanded diameter portion 12 is, for example, 0.5 nm to 50 nm, preferably 1.1 nm to 40 nm, and more preferably 1.1 nm to 3.3 nm. Eis, for example, the pore size of the precursor material (A) described later and the average particle size D of the functional material 20 to be enclosed. C The inner diameter D of the expanded diameter portion 12 depends on E is a size capable of encapsulating the functional substance 20.
[0027] The framework 10 is composed of a zeolite-type compound. Examples of the zeolite-type compound include silicate compounds such as zeolite (aluminosilicate), cation-exchanged zeolite, and silicalite, zeolite-related compounds such as aluminoborates, aluminoarsenates, and germanates, and phosphate-based zeolite-like substances such as molybdenum phosphate. Among these, the zeolite-type compound is preferably a silicate compound.
[0028] The framework structure of the zeolite compound is selected from FAU type (Y type or X type), MTW type, MFI type (ZSM-5), FER type (ferrierite), LTA type (A type), MWW type (MCM-22), MOR type (mordenite), LTL type (L type), BEA type (beta type), etc., preferably MFI type, more preferably ZSM-5. In the zeolite compound, a plurality of pores having a pore size according to each framework structure are formed, for example, the maximum pore size of the MFI type is 0.636 nm (6.36 Å) and the average pore size is 0.560 nm (5.60 Å).
[0029] Hereinafter, a detailed description will be given of the case where the functional material 20 is at least one of metal oxide fine particles and metal fine particles (hereinafter, these may be collectively referred to as "fine particles").
[0030] When the functional material 20 is the above-mentioned fine particles, the fine particles 20 may be primary particles or secondary particles formed by aggregation of the primary particles. C is preferably the average inner diameter D of the passage 11 F and the inner diameter D of the expanded diameter portion 12 is larger than E The following is true: F <D C ≦D E). In the passage 11, such microparticles 20 are preferably enclosed in the enlarged diameter portions 12, and the movement of the microparticles 20 in the skeleton 10 is restricted. Therefore, even if the microparticles 20 are subjected to an external force from the fluid, the movement of the microparticles 20 in the skeleton 10 is restricted, and the microparticles 20, 20, ... enclosed in the enlarged diameter portions 12, 12, ... dispersed and arranged in the passage 11 of the skeleton 10 can be effectively prevented from contacting each other.
[0031] In addition, when the functional material 20 is metal oxide fine particles, the dispersibility of the metal oxide fine particles 20 is determined by the average particle size D C The average particle diameter D of the metal oxide fine particles 20 is less than 30 nm, preferably less than 5.0 nm, more preferably 3.3 nm or less, and further preferably less than 2.0 nm. C The lower limit of the average inner diameter D of the passage 11 is not particularly limited, but is preferably 0.1 nm or more, and more preferably 1.0 nm or more, in both the case of the primary particles and the secondary particles. F Average particle size D of metal oxide fine particles 20 C Percentage of (D C / D F ) is preferably 0.06 to 500, more preferably 0.1 to 45, further preferably 1.1 to 45, and particularly preferably 1.3 to 3.5. Furthermore, when the functional substance 20 is metal oxide microparticles, the metal element (M) of the metal oxide microparticles is preferably contained in an amount of 0.5 to 2.5 mass % relative to the functional structure 1, and more preferably 0.5 to 1.5 mass % relative to the functional structure 1. For example, when the metal element (M) is Co, the content (mass %) of the Co element is expressed as {(mass of Co element) / (mass of all elements in the functional structure 1)}×100.
[0032] The metal oxide microparticles may be composed of a metal oxide, and may be composed of, for example, a single metal oxide or a mixture of two or more metal oxides. In this specification, the term "metal oxide" (as a material) constituting the metal oxide microparticles means an oxide containing one metal element (M) and a composite oxide containing two or more metal elements (M), and is a general term for oxides containing one or more metal elements (M).
[0033] Examples of such metal oxides include cobalt oxide (CoO x ), Nickel oxide (NiO x ), iron oxide (FeO x ), copper oxide (CuO x ), zirconium oxide (ZrO x ), cerium oxide (CeO x ), aluminum oxide (AlO x ), niobium oxide (NbO x ), titanium dioxide (TiO x ), bismuth oxide (BiO x ), molybdenum oxide (MoO x ), vanadium oxide (VO x ), chromium oxide (CrO x ) and the like, and it is preferable to use one or more of the above as the main component.
[0034] In addition, when the functional material 20 is metal fine particles, the dispersibility of the metal fine particles 20 is determined by the average particle size D C The average particle diameter D of the metal particles 20 is less than 30 nm, preferably less than 5.0 nm, and more preferably less than 2.0 nm. C The lower limit of the average inner diameter D of the passage 11 is not particularly limited, but is preferably 0.08 nm or more, and more preferably 0.8 nm or more, in both the case of the primary particles and the secondary particles. F Average particle size D of metal particles 20 C Percentage of (D C / D F) is preferably 0.05 to 300, more preferably 0.1 to 30, further preferably 1.1 to 30, and particularly preferably 1.3 to 3.5. When the functional substance 20 is a metal microparticle, the metal element (M) of the metal microparticle is preferably contained in the functional structure 1 at 0.5 to 2.5 mass %, and more preferably at 0.5 to 1.5 mass %.
[0035] The metal microparticles may be composed of a non-oxidized metal, and may be composed of, for example, a single metal or a mixture of two or more metals. In this specification, the term "metal" (as a material) constituting the metal microparticles means a simple metal containing one metal element (M) and a metal alloy containing two or more metal elements (M), and is a general term for metals containing one or more metal elements.
[0036] Examples of such metals include platinum (Pt), palladium (Pd), ruthenium (Ru), nickel (Ni), cobalt (Co), molybdenum (Mo), tungsten (W), iron (Fe), chromium (Cr), cerium (Ce), copper (Cu), magnesium (Mg), and aluminum (Al). It is preferable to use one or more of the above as the main component.
[0037] From the viewpoint of durability, the functional material 20 is preferably metal oxide fine particles.
[0038] Moreover, the ratio of silicon (Si) constituting the framework 10 to the metal element (M) constituting the microparticles 20 (atomic ratio Si / M) is preferably 10 to 1000, more preferably 50 to 200. If the ratio is more than 1000, the activity may be low and the effect as a functional material may not be sufficiently obtained. On the other hand, if the ratio is less than 10, the ratio of the microparticles 20 becomes too large, and the strength of the framework 10 tends to decrease. Note that the microparticles 20 referred to here refer to microparticles present inside or supported by the framework 10, and do not include microparticles attached to the outer surface of the framework 10.
[0039] [Functions of functional structures] As described above, the functional structure 1 includes a skeleton 10 having a porous structure and at least one functional substance 20 present in the skeleton 10. The functional structure 1 exerts a function according to the functional substance 20 by contacting the functional substance 20 present in the skeleton 10 with a fluid. Specifically, the fluid that contacts the outer surface 10a of the functional structure 1 flows into the skeleton 10 through the holes 11a formed in the outer surface 10a, is guided into the passage 11, moves through the passage 11, and exits the functional structure 1 through another hole 11a. In the path in which the fluid moves through the passage 11, the fluid comes into contact with the functional substance 20 held in the passage 11, causing a reaction (e.g., a catalytic reaction) according to the function of the functional substance 20. In addition, the functional structure 1 has a molecular sieving function because the skeleton 10 has a porous structure.
[0040] First, the molecular sieving ability of the functional structure 1 will be described with reference to FIG. 2(a) using an example in which the fluid is a liquid containing benzene, propylene, and mesitylene. As shown in FIG. 2(a), compounds (e.g., benzene, propylene) composed of molecules having a size equal to or smaller than the pore size of the hole 11a, in other words, equal to or smaller than the inner diameter of the passage 11, can penetrate into the framework 10. On the other hand, compounds (e.g., mesitylene) composed of molecules having a size larger than the pore size of the hole 11a cannot penetrate into the framework 10. In this way, when the fluid contains multiple types of compounds, the reaction of the compounds that cannot penetrate into the framework 10 is restricted, and the compounds that can penetrate into the framework 10 can be reacted.
[0041] Of the compounds produced in the framework 10 by the reaction, only compounds composed of molecules having a size equal to or smaller than the diameter of the holes 11a can escape to the outside of the framework 10 through the holes 11a and are obtained as reaction products. On the other hand, compounds that cannot escape to the outside of the framework 10 through the holes 11a can be escaped to the outside of the framework 10 if they are converted into compounds composed of molecules of a size that can escape to the outside of the framework 10. In this way, by using the functional structure 1, a specific reaction product can be selectively obtained.
[0042] In the functional structure 1, as shown in FIG. 2(b), a functional substance 20 is preferably included in the expanded diameter portion 12 of the passage 11. When the functional substance 20 is metal oxide fine particles, the average particle diameter D of the metal oxide fine particles is C is the average inner diameter D of passage 11 F The inner diameter D of the expanded portion 12 is larger than E If it is smaller than (D F <D C <D E ), small passages 13 are formed between the metal oxide fine particles and the expanded diameter section 12. Then, as shown by the arrows in FIG. 2(b), the fluid that has entered the small passages 13 comes into contact with the metal oxide fine particles. Since each metal oxide fine particle is enclosed by the expanded diameter section 12, movement within the framework 10 is restricted. This prevents the metal oxide fine particles from agglomerating together within the framework 10. As a result, a large contact area between the metal oxide fine particles and the fluid can be stably maintained. Furthermore, in the functional structure 1, the metal fine particles and metal oxide fine particles have an average particle size D C Since the highly dispersed state of less than 30 nm is maintained, high catalytic activity and other activities can be maintained for a long period of time.
[0043] Next, a case where the functional material 20 has a catalytic function will be described. Specifically, when the functional material 20 is iron oxide (FeO x) fine particles, and a case where dodecylbenzene, a heavy oil, is infiltrated into the framework 10 of the functional structure 1 will be described as an example. When dodecylbenzene infiltrates into the framework 10, as shown below, the dodecylbenzene is decomposed into various alcohols and ketones by an oxidative decomposition reaction. Furthermore, benzene, a light oil, is generated from ketone (acetophenone in this case), which is one of the decomposition products. This means that the functional material 20 functions as a catalyst in the oxidative decomposition reaction. In this way, heavy oil can be converted into light oil by using the functional structure 1. Conventionally, hydrocracking using hydrogen was performed to convert heavy oil into light oil. In contrast, hydrogen is not required by using the functional structure 1. Therefore, it can be used to convert heavy oil into light oil even in areas where it is difficult to supply hydrogen. In addition, by eliminating the need for hydrogen, it is possible to realize a reduction in cost, and it is expected that the use of heavy oil, which has not been fully utilized until now, will be promoted.
[0044] [ka] [ka]
[0045] [Method of manufacturing functional structures] Fig. 3 is a flowchart showing a method for producing the functional structure 1 of Fig. 1. Hereinafter, an example of the method for producing the functional structure will be described taking as an example a case where the functional substance present in the framework is metal oxide fine particles.
[0046] (Step S1: Preparation process) First, a precursor material (A) for obtaining a porous structure framework composed of a zeolite-type compound is prepared as shown in Fig. 3. The precursor material (A) is preferably a regular mesoporous substance, and can be appropriately selected depending on the type (composition) of the zeolite-type compound that constitutes the framework of the functional structure.
[0047] Here, when the zeolite-type compound constituting the framework of the functional structure is a silicate compound, the regular mesoporous material is preferably a compound consisting of a Si-O framework in which pores with a pore diameter of 1 to 50 nm are uniform in size and regularly developed in one, two or three dimensions. Such regular mesoporous materials can be obtained as various synthetic products depending on the synthesis conditions, and specific examples of synthetic products include SBA-1, SBA-15, SBA-16, KIT-6, FSM-16, MCM-41, etc., and among them, MCM-41 is preferable. The pore diameter of SBA-1 is 10 to 30 nm, the pore diameter of SBA-15 is 6 to 10 nm, the pore diameter of SBA-16 is 6 nm, the pore diameter of KIT-6 is 9 nm, the pore diameter of FSM-16 is 3 to 5 nm, and the pore diameter of MCM-41 is 1 to 10 nm. Examples of such regular mesoporous substances include mesoporous silica, mesoporous aluminosilicate, and mesoporous metallosilicate.
[0048] The precursor material (A) may be either a commercially available product or a synthetic product. The precursor material (A) can be synthesized by a known method for synthesizing regular mesoporous materials. For example, a mixed solution containing raw materials containing the constituent elements of the precursor material (A) and a template agent for defining the structure of the precursor material (A) is prepared, and the pH is adjusted as necessary to perform hydrothermal treatment (hydrothermal synthesis). Thereafter, the precipitate (product) obtained by the hydrothermal treatment is collected (for example, filtered), washed and dried as necessary, and further calcined to obtain the precursor material (A), which is a powdered regular mesoporous material. Here, the solvent for the mixed solution can be, for example, water, an organic solvent such as alcohol, or a mixed solvent thereof. The raw material is selected according to the type of framework, and examples thereof include silica agents such as tetraethoxysilane (TEOS), fumed silica, and quartz sand. As the template agent, various surfactants, block copolymers, etc. can be used, and it is preferable to select according to the type of the ordered mesoporous material. For example, when preparing MCM-41, a surfactant such as hexadecyltrimethylammonium bromide is suitable. The hydrothermal treatment can be carried out, for example, in a closed vessel under the treatment conditions of 80 to 800°C, 5 to 240 hours, and 0 to 2000 kPa. The calcination treatment can be carried out, for example, in air under the treatment conditions of 350 to 850°C, 2 to 30 hours.
[0049] (Step S2: Impregnation process) Next, the prepared precursor material (A) is impregnated with a metal-containing solution to obtain a precursor material (B).
[0050] The metal-containing solution may be any solution containing a metal component (e.g., metal ion) corresponding to the metal element (M) constituting the metal oxide microparticles of the functional structure, and may be prepared, for example, by dissolving a metal salt containing the metal element (M) in a solvent. Examples of such metal salts include metal salts such as chlorides, hydroxides, oxides, sulfates, and nitrates, and among these, nitrates are preferred. Examples of the solvent that can be used include water, organic solvents such as alcohol, and mixtures thereof.
[0051] The method of impregnating the precursor material (A) with the metal-containing solution is not particularly limited, but for example, it is preferable to add the metal-containing solution in small amounts in multiple batches while stirring the powdered precursor material (A) before the firing step described below. In addition, from the viewpoint of making it easier for the metal-containing solution to penetrate into the pores of the precursor material (A), it is preferable to add a surfactant as an additive to the precursor material (A) before adding the metal-containing solution. Such an additive has the function of coating the outer surface of the precursor material (A), and is thought to suppress the adhesion of the metal-containing solution added thereafter to the outer surface of the precursor material (A), making it easier for the metal-containing solution to penetrate into the pores of the precursor material (A).
[0052] Examples of such additives include nonionic surfactants such as polyoxyethylene oleyl ether (O-15), polyoxyethylene alkyl ether, and polyoxyethylene alkyl phenyl ether. These surfactants have a large molecular size and cannot penetrate into the pores of the precursor material (A), so they do not adhere to the inside of the pores and are considered not to hinder the metal-containing solution from penetrating into the pores. The amount of the additive added to the precursor material (A) is preferably adjusted appropriately in consideration of the dispersibility of the metal element (M) contained in the metal-containing solution to be impregnated into the precursor material (A). For example, the molar ratio (Si / additive) of silicon (Si) constituting the precursor material (A) to the additive (surfactant) added to the precursor material (A) is preferably 25 or less in terms of obtaining dispersibility, more preferably 10 or less in terms of obtaining higher dispersibility, and particularly preferably 5 or less.
[0053] In addition, the amount of the metal-containing solution added to the precursor material (A) is preferably adjusted appropriately in consideration of the amount of the metal element (M) contained in the metal-containing solution impregnated into the precursor material (A) (i.e., the amount of the metal element (M) to be contained in the precursor material (B)). For example, before the firing step described below, the amount of the metal-containing solution added to the precursor material (A) is preferably adjusted to be 10 to 1000, more preferably 50 to 200, in terms of the ratio of silicon (Si) constituting the precursor material (A) to the metal element (M) contained in the metal-containing solution added to the precursor material (A) (atomic ratio Si / M). For example, in the case where a surfactant is added to the precursor material (A) as an additive before the addition of the metal-containing solution to the precursor material (A), the amount of the metal-containing solution added to the precursor material (A) is adjusted to be 50 to 200 in terms of the atomic ratio Si / M, so that the metal element (M) of the metal oxide fine particles can be contained in an amount of 0.5 to 2.5 mass% relative to the functional structure. The amount of metal element (M) present inside the pores of the precursor material (B) is roughly proportional to the amount of metal-containing solution added to the precursor material (A) under the same conditions such as the metal concentration of the metal-containing solution, the presence or absence of the additive, and other conditions such as temperature and pressure. The amount of metal element (M) present in the precursor material (B) is also proportional to the amount of metal element constituting the metal oxide microparticles present in the framework of the functional structure. Therefore, by controlling the amount of metal-containing solution added to the precursor material (A) within the above range, the metal-containing solution can be sufficiently impregnated into the pores of the precursor material (A), and the amount of metal oxide microparticles present in the framework of the functional structure can be adjusted.
[0054] After the precursor material (A) is impregnated with the metal-containing solution, a washing process may be performed as necessary. As the washing solution, water, an organic solvent such as alcohol, or a mixture of these can be used. In addition, after the precursor material (A) is impregnated with the metal-containing solution and washed as necessary, it is preferable to further perform a drying process. Examples of the drying process include natural drying for about one night, and high-temperature drying at 150°C or less. Note that if the calcination process described below is performed while a large amount of moisture contained in the metal-containing solution or the moisture of the washing solution remains in the precursor material (A), the skeleton structure of the precursor material (A) as a regular mesoporous material may be destroyed, so it is preferable to dry it thoroughly.
[0055] (Step S3: Firing process) Next, precursor material (A) for obtaining a porous framework composed of a zeolite-type compound is impregnated with a metal-containing solution to obtain precursor material (B), which is then calcined to obtain precursor material (C).
[0056] The calcination treatment is preferably carried out in air at 350 to 850° C. for 2 to 30 hours. By such a calcination treatment, the metal component impregnated in the pores of the ordered mesoporous material undergoes crystal growth, forming metal oxide fine particles in the pores.
[0057] (Step S4: Hydrothermal treatment process) Next, a mixed solution is prepared by mixing the precursor material (C) and a structure directing agent, and the precursor material (C) obtained by calcining the precursor material (B) is subjected to a hydrothermal treatment to obtain a functional structure.
[0058] The structure-directing agent is a template agent for determining the skeletal structure of the skeleton of the functional structure, and for example, a surfactant can be used. The structure-directing agent is preferably selected according to the skeleton structure of the skeleton of the functional structure, and for example, surfactants such as tetramethylammonium bromide (TMABr), tetraethylammonium bromide (TEABr), and tetrapropylammonium bromide (TPABr) are suitable.
[0059] The precursor material (C) and the structure-directing agent may be mixed during the hydrothermal treatment process or before the hydrothermal treatment process. The method for preparing the mixed solution is not particularly limited, and the precursor material (C), the structure-directing agent, and the solvent may be mixed at the same time, or the precursor material (C) and the structure-directing agent may be dispersed in the solvent in their respective solutions, and then the respective dispersion solutions may be mixed. As the solvent, for example, water, an organic solvent such as alcohol, or a mixture of these may be used. It is also preferable to adjust the pH of the mixed solution using an acid or a base before performing the hydrothermal treatment.
[0060] The hydrothermal treatment can be carried out by a known method, and is preferably carried out in a sealed container under the treatment conditions of 80 to 800°C, 5 to 240 hours, and 0 to 2000 kPa. The hydrothermal treatment is preferably carried out in a basic atmosphere. Although the reaction mechanism here is not necessarily clear, by carrying out the hydrothermal treatment using the precursor material (C) as a raw material, the skeleton structure of the precursor material (C) as a regular mesoporous substance gradually collapses, but the positions of the metal oxide fine particles inside the pores of the precursor material (C) are generally maintained, and a new skeleton structure (porous structure) as the skeleton of the functional structure is formed by the action of the structure-directing agent. The functional structure thus obtained comprises a skeleton of a porous structure and metal oxide fine particles contained in the skeleton, and the skeleton further has a passage in which a plurality of pores are connected to each other due to the porous structure, and at least a part of the metal oxide fine particles is present in the passage of the skeleton.
[0061] The precipitate (functional structure) obtained after the hydrothermal treatment is preferably washed, dried and calcined as necessary after recovery (for example, filtration). As the washing solution, water, an organic solvent such as alcohol, or a mixture of these can be used. As the drying treatment, natural drying for about one night or high-temperature drying at 150°C or less can be used. If the precipitate is calcined while a large amount of moisture remains, the skeleton structure as the skeleton of the functional structure may be destroyed, so it is preferable to dry it thoroughly. In addition, the calcination treatment can be performed, for example, in air at 350 to 850°C for 2 to 30 hours. By such a calcination treatment, the structure-directing agent attached to the functional structure is burned off. In addition, the functional structure can be used as it is without calcining the precipitate after recovery depending on the purpose of use. For example, when the environment in which the functional structure is used is a high-temperature environment in an oxidizing atmosphere, the structure-directing agent is burned off by exposing it to the use environment for a certain period of time, and the functional structure can be obtained similar to that obtained by calcination treatment, so that it can be used as it is. In addition, in the present embodiment, in the above-mentioned hydrothermal treatment step, a mixed solution is prepared by mixing the precursor material (C) and the structure-directing agent, and the precursor material (C) is hydrothermally treated. However, this is not limited thereto, and the precursor material (C) may be hydrothermally treated without mixing the precursor material (C) with the structure-directing agent.
[0062] Although the above has been described by taking the example of a method for producing a functional structure in which the functional substance is metal oxide fine particles, a functional structure can be produced in the same manner as above when the functional substance is metal fine particles. For example, after obtaining a functional structure having metal oxide particles as described above, a reduction treatment is performed under a reducing gas atmosphere such as hydrogen gas to obtain a functional structure in which metal fine particles are present in a framework. In this case, the metal oxide fine particles present in the framework are reduced to form metal fine particles corresponding to the metal element (M) constituting the metal oxide fine particles. Alternatively, by using a metal element (M) contained in a metal-containing solution to be impregnated into the precursor material (A) as a metal species that is difficult to oxidize (e.g., a noble metal), the metal fine particles can be crystal-grown in the firing step (step S3), and then a hydrothermal treatment is performed to obtain a functional structure in which metal fine particles are present in a framework.
[0063] [Modification of functional structure 1] FIG. 4 is a schematic diagram showing a modified example of the functional structure 1 of FIG. The functional structure 1 in Figure 1 is shown to have a skeleton 10 and a functional substance 20 contained within the skeleton 10, but is not limited to this configuration. For example, as shown in Figure 4, the functional structure 2 may further have at least one functional substance 30 held on the outer surface 10a of the skeleton 10.
[0064] This functional material 30 is a material that exerts one or more functions. The function possessed by the functional material 30 may be the same as or different from the function possessed by the functional material 20. Specific examples of the functions possessed by the functional material 30 are the same as those described for the functional material 20, and among them, it is preferable that the functional material 30 has a catalytic function, in which case the functional material 30 is a catalytic material. In addition, when both the functional materials 20 and 30 are materials having the same function, the material of the functional material 30 may be the same as or different from the material of the functional material 20. According to this configuration, the content of the functional material held in the functional structure 2 can be increased, and the function exertion of the functional material can be further promoted.
[0065] In this case, the content of the functional material 20 present in the framework 10 is preferably greater than the content of the functional material 30 held on the outer surface 10a of the framework 10. This allows the function of the functional material 20 held inside the framework 10 to predominate, and the function of the functional material is stably exerted.
[0066] Although the functional structure according to the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and various modifications and changes are possible based on the technical concept of the present invention. EXAMPLES
[0067] (Examples 1 to 576) [Synthesis of precursor material (A)] A mixed aqueous solution was prepared by mixing a silica agent (tetraethoxysilane (TEOS), manufactured by Wako Pure Chemical Industries, Ltd.) with a surfactant as a template agent, and the pH was appropriately adjusted. The solution was subjected to hydrothermal treatment at 80 to 350°C for 100 hours in a sealed container. The resulting precipitate was then filtered, washed with water and ethanol, and further calcined in air at 600°C for 24 hours to obtain precursor materials (A) of the types and pore sizes shown in Tables 1 to 16. The following surfactants were used according to the type of precursor material (A) ("Type of precursor material (A): Surfactant"). MCM-41: Hexadecyltrimethylammonium bromide (CTAB) (Wako Pure Chemical Industries, Ltd.) SBA-1: Pluronic P123 (BASF)
[0068] [Preparation of precursor materials (B) and (C)] Next, metal-containing aqueous solutions were prepared by dissolving metal salts containing the metal elements (M) constituting the metal oxide microparticles of the types shown in Tables 1 to 16 in water. The metal salts used were as follows, depending on the type of metal oxide microparticles ("metal oxide microparticles: metal salts"). CoO x : Cobalt(II) nitrate hexahydrate (manufactured by Wako Pure Chemical Industries, Ltd.) NiOx Nickel (II) nitrate hexahydrate (Wako Pure Chemical Industries, Ltd.) FeO x :Iron(III) nitrate nonahydrate (manufactured by Wako Pure Chemical Industries, Ltd.) CuO x : Copper(II) nitrate trihydrate (manufactured by Wako Pure Chemical Industries, Ltd.)
[0069] Next, the metal-containing aqueous solution was added in small amounts in several batches to the powdered precursor material (A), and the mixture was dried at room temperature (20° C.±10° C.) for 12 hours or more to obtain a precursor material (B).
[0070] In addition, when the condition of the presence or absence of additives shown in Tables 1 to 16 is "present," a pretreatment was performed by adding an aqueous solution of polyoxyethylene (15) oleyl ether (NIKKOL BO-15V, manufactured by Nikko Chemicals Co., Ltd.) (represented as "O-15" in Tables 1 to 16) as an additive to the precursor material (A) before adding the metal-containing aqueous solution, and then the metal-containing aqueous solution was added as described above. The ratio of silicon (Si) constituting the precursor material (A) to the amount of additive (O-15) added to the precursor material (A) (atomic number ratio: Si / O-15) was adjusted to the value in Tables 1 to 16. In addition, when the condition of the presence or absence of additives is "not present," the pretreatment with the additives as described above was not performed.
[0071] In addition, the amount of metal-containing aqueous solution added to the precursor material (A) was adjusted so that the ratio of silicon (Si) constituting the precursor material (A) to the metal element (M) contained in the metal-containing aqueous solution (atomic number ratio: Si / M) would be one of the values shown in Tables 1 to 16.
[0072] Next, the precursor material (B) impregnated with the metal-containing aqueous solution obtained as described above was calcined in air at 600° C. for 24 hours to obtain a precursor material (C).
[0073] [Synthesis of functional structures] The precursor material (C) obtained as described above was mixed with a structure directing agent shown in Tables 1 to 16 to prepare a mixed aqueous solution, which was then subjected to hydrothermal treatment in a sealed container at 80 to 350°C under the conditions of pH and time shown in Tables 1 to 16. Thereafter, the resulting precipitate was filtered off, washed with water, dried at 100°C for 12 hours or more, and further calcined in air at 600°C for 24 hours to obtain functional structures having frameworks and metal oxide fine particles as functional substances shown in Tables 1 to 16 (Examples 1 to 576).
[0074] Comparative Example 1 In Comparative Example 1, MFI-type silicalite was mixed with cobalt oxide powder (II, III) (manufactured by Sigma-Aldrich Japan LLC) having an average particle size of 50 nm or less to obtain silica as a framework. A functional structure was obtained in which cobalt oxide fine particles were attached as a functional material to the outer surface of the silicalite. The MFI type silicalite was synthesized in the same manner as in Examples 76 to 81, except for the step of adding the metal.
[0075] Comparative Example 2 In Comparative Example 2, MFI type silicalite was synthesized in the same manner as in Comparative Example 1, except that the step of adhering cobalt oxide fine particles was omitted.
[0076] [evaluation] Various characteristics of the functional structures of the above examples and the silicalite of the comparative example were evaluated under the conditions shown below.
[0077] [A] Cross-section observation For the functional structures of the above-mentioned Examples and the silicalite with cobalt oxide microparticles attached thereto of the Comparative Example, observation samples were prepared by a pulverization method, and cross-sections were observed using a transmission electron microscope (TEM) (TITAN G2, manufactured by FEI). As a result, it was confirmed that the functional material was present and held inside the framework made of silicalite or zeolite in the functional structures of the above examples, whereas in the silicalite of Comparative Example 1, the functional material was only attached to the outer surface of the framework and was not present inside the framework. In addition, for the functional structures in the above examples in which the metal oxide was iron oxide fine particles (FeOx), cross sections were cut out by FIB (focused ion beam) processing and examined with a SEM (SU8020 , manufactured by Hitachi High-Technologies Corporation), and EDX (X-Max, manufactured by Horiba, Ltd.) Cross-sectional elemental analysis was performed using a 3D scanner, and the element Fe was detected from the inside of the skeleton. The above-mentioned cross-sectional observations by TEM and SEM / EDX confirmed the presence of iron oxide particles inside the framework.
[0078] [B] Average inner diameter of the pathways in the framework and average particle size of the functional material In the TEM image taken by the cross-sectional observation performed in the above evaluation [A], 500 passages of the skeleton were randomly selected, the long and short diameters of each were measured, and the inner diameter of each was calculated from the average value (N=500). The average inner diameter was then calculated to obtain the average inner diameter D F Similarly, for the functional substance, 500 functional substances were randomly selected from the above TEM image, and the particle size of each was measured (N=500), and the average value was calculated to obtain the average particle size D C The results are shown in Tables 1 to 16. In addition, to confirm the average particle size and dispersion state of the functional material, analysis was performed using SAXS (small angle X-ray scattering). SAXS measurements were performed using the beamline BL19B2 of Spring-8. The obtained SAXS data was fitted with a spherical model using the Guinier approximation method to calculate the particle size. The particle size was measured for functional structures in which the metal oxide was iron oxide fine particles. For comparison, commercially available iron oxide fine particles (manufactured by Wako) were observed and measured using a SEM. As a result, while the commercially available product contains randomly distributed iron oxide particles of various sizes in the range of particle diameters from about 50 nm to 400 nm, the functional structures of the examples, which have an average particle diameter of 1.2 nm to 2.0 nm as determined from TEM images, also showed scattering peaks of particle diameters of 10 nm or less in the SAXS measurement results. From the SAXS measurement results and the cross-sectional measurement results by SEM / EDX, it was found that functional substances with particle diameters of 10 nm or less exist within the framework in a uniform particle size and in a highly dispersed state.
[0079] [C] Relationship between the amount of metal-containing solution added and the amount of metal encapsulated within the framework Functional structures were prepared by encapsulating metal oxide particles in the framework with the addition amount of atomic ratios Si / M=50, 100, 200, 1000 (M=Co, Ni, Fe, Cu), and then the amount of metal (mass%) encapsulated in the framework of the functional structures prepared with the above addition amount was measured. In this measurement, the functional structures with atomic ratios Si / M=100, 200, 1000 were prepared by adjusting the amount of metal-containing solution added in the same manner as the functional structures with atomic ratios Si / M=100, 200, 1000 in Examples 1 to 576, respectively, and the functional structures with atomic ratios Si / M=50 were prepared in the same manner as the functional structures with atomic ratios Si / M=100, 200, 1000, except that the amount of metal-containing solution added was different. The amount of metal was determined by ICP (inductively coupled plasma) alone or a combination of ICP and XRF (X-ray fluorescence analysis). XRF (energy dispersive X-ray fluorescence analyzer "SEA1200VX", manufactured by SSI NanoTechnology Co., Ltd.) was performed under vacuum conditions with an accelerating voltage of 15 kV (using a Cr filter) or 50 kV (using a Pb filter). XRF is a method to calculate the amount of metal present by fluorescence intensity, and quantitative values (mass % conversion) cannot be calculated by XRF alone. Therefore, the amount of metal in the functional structure to which metal was added at Si / M=100 was quantified by ICP analysis, and the amount of metal in the functional structure to which metal was added at Si / M=50 and less than 100 was calculated based on the results of XRF measurement and ICP measurement. As a result, it was confirmed that, at least within the atomic ratio Si / M range of 50 to 1000, the amount of metal encapsulated in the functional structure increases with an increase in the amount of metal-containing solution added.
[0080] [C] Performance evaluation The catalytic ability (performance) of the functional material (catalyst material) was evaluated for the functional structures of the above-mentioned Examples and the silicalite of the Comparative Example.
[0081] (1) Measurement of average particle size and confirmation of dispersibility The average particle size and dispersibility of the catalyst were measured using small angle X-ray scattering (SAXS) (Rigaku Corporation, product name: Nano-viewer IP). As an index of dispersibility, when the particle size of the catalyst was less than 2.0 nm, the dispersibility was evaluated as particularly good (◎), when it was 2.0 nm or more but less than 5.0 nm, the dispersibility was evaluated as good (○), and when it was 5.0 nm or more, the dispersibility was evaluated as normal (△).
[0082] (2) Catalytic activity The catalytic activity was evaluated under the following conditions. First, 0.2 g of the functional structure was packed into a normal pressure flow reactor, and nitrogen gas (N2) was used as the carrier gas (5 ml / min) at 400°C for 2 hours. We carried out a decomposition reaction of the benzoyl peroxidase (benzoyl substance). After the reaction was completed, the recovered product gas and liquid were analyzed for their components by gas chromatography / mass spectrometry (GC / MS). The GC (Thermo Fisher Scientific, Inc., detector: thermal conductivity detector) was used, and the analysis equipment for the product liquid was a TRACE DSQ (Thermo Fisher Scientific, Inc., detector: thermal conductivity detector). The detector used was a mass detector manufactured by Intificiq Co., Ltd., and the ionization method was EI (ion source temperature 250°C, MS transfer line temperature 320°C, detector: thermal conductivity detector). Furthermore, based on the results of the above component analysis, the yield (mol%) of compounds having a molecular weight smaller than that of butylbenzene (specifically, benzene, toluene, ethylbenzene, styrene, cumene, methane, ethane, ethylene, propane, propylene, butane, butene, etc.) was determined. The yield of the above compounds was calculated as the percentage (mol%) of the total amount (mol) of the substances of compounds having a molecular weight smaller than that of butylbenzene contained in the product liquid relative to the amount (mol) of butylbenzene before the start of the reaction. In this example, when the yield of compounds having a smaller molecular weight than butylbenzene contained in the product liquid was 40 mol% or more, the catalytic activity (resolution) was judged to be excellent and marked with "◎", when it was 25 mol% or more and less than 40 mol%, the catalytic activity was judged to be good and marked with "○", when it was 10 mol% or more and less than 25 mol%, the catalytic activity was judged to be not good but to be at an acceptable level (passable) and marked with "△", and when it was less than 10 mol%, the catalytic activity was judged to be poor (unacceptable) and marked with "X".
[0083] For Comparative Examples 1 and 2, the same performance evaluations as those in the above evaluations (1) and (2) were carried out. It should be noted that Comparative Example 2 is the framework itself and does not have any functional substance. Therefore, in the above performance evaluation, only the framework of Comparative Example 2 was filled in place of the functional structure. The results are shown in Tables 1 to 16.
[0084] [Table 1]
[0085] [Table 2]
[0086] [Table 3]
[0087] [Table 4]
[0088]
Table 5
[0089]
Table 6
[0090]
Table 7
[0091]
Table 8
[0092]
Table 9
[0093]
Table 10
[0094]
Table 11
[0095]
Table 12
[0096]
Table 13
[0097]
Table 14
[0098]
Table 15
[0099] [Table 16]
[0100] As is clear from Tables 1 to 16, the functional structures (Examples 1 to 576) in which it was confirmed by cross-sectional observation that a functional substance was retained inside the skeleton showed superior catalytic activity in the decomposition reaction of butylbenzene compared to a functional structure in which a functional substance was simply attached to the outer surface of the skeleton (Comparative Example 1) or the skeleton itself having no functional substance (Comparative Example 2).
[0101] Furthermore, when the dispersibility of the functional substance inside the framework was excellent, excellent catalytic activity was obtained in the decomposition reaction of butylbenzene. In particular, in the example in which the ratio (atomic ratio: Si / O-15) of silicon (Si) constituting the precursor material (A) to the amount of additive (O-15) added to the precursor material (A) was 5, the dispersibility judged based on the particle size was further improved and even more excellent catalytic activity was obtained, compared to the example in which the ratio was 25 and the example in which the additive (O-15) was not added.
[0102] In addition, the relationship between the amount of metal (mass%) encapsulated within the framework of the functional structure measured in the above evaluation [C] and the yield (mol%) of compounds with molecular weights smaller than that of butylbenzene contained in the product solution was evaluated. The evaluation method was the same as that used in "(1) Catalytic activity" in the above [D] "Performance evaluation". As a result, in each example, it was found that when the amount of metal-containing solution added to the precursor material (A) was 50 to 200, converted into the atomic ratio Si / M (M = Fe) (the content of the metal element (M) of the metal oxide microparticles relative to the functional structure was 0.5 to 2.5 mass%), the yield of compounds having a smaller molecular weight than butylbenzene contained in the product liquid was 32 mol% or more, and the catalytic activity in the decomposition reaction of butylbenzene was above the acceptable level.
[0103] On the other hand, the functional structures of Comparative Examples 1 to 4, in which functional substances were attached only to the outer surface of the skeleton, had inferior catalytic activity in the decomposition reaction of butylbenzene compared to the functional structures of Examples 1 to 576, similar to the skeleton of Reference Example 1 itself, which had no functional substance.
[0104] On the other hand, the framework of Comparative Example 2 itself, which did not have any functional substance, showed almost no catalytic activity in the decomposition reaction of butylbenzene, and had inferior catalytic activity compared to the functional structures of Examples 1 to 576. [Explanation of symbols]
[0105] 1 Functional structure 10 Skeleton 10a outer surface 11 Passage 11a hole 12 Expanded diameter part 20 Functional substances 30 Functional substances D C Average particle size D F Average inner diameter D E Inner diameter
Claims
1. A porous framework composed of a zeolite compound; At least one functional substance present within the scaffold; Equipped with the functional substance is a substance that exerts a catalytic function alone or in cooperation with the framework, the functional material is an oxide of one metal selected from the group consisting of Co, Ni, and Fe; The framework has passages communicating with each other, the passage has one of one-dimensional pores, two-dimensional pores, and three-dimensional pores defined by the framework structure of the zeolite-type compound, and an expanded portion different from any of the one-dimensional pores, the two-dimensional pores, and the three-dimensional pores; The functional material is present in at least the passages of the framework, and the average particle size of the functional material is 5.00 nm or more and less than 30 nm; A functional structure, wherein a ratio of an average particle size of the functional material to an average inner diameter of the passage is 6.76 to 35.71, and the average inner diameter of the passage is calculated from an average value of a short axis and a long axis of a pore constituting any one of the one-dimensional pores, the two-dimensional pores, and the three-dimensional pores.
2. 2. The functional structure according to claim 1, wherein a ratio of an average particle size of said functional substance to an average inner diameter of said passages is 8.93 to 35.
71.
3. 3. The functional structure according to claim 1, excluding those in which the average major axis of the framework is 50 to 1000 nm.
4. The functional structure according to any one of claims 1 to 3, excluding those in which the framework structure of the zeolite type compound is an MFI type.
5. A functional structure described in any one of claims 1 to 4, wherein the functional substance is present in an encapsulated form at least in the expanded diameter portion.
6. The functional structure according to any one of claims 1 to 5, wherein the enlarged diameter portion connects a plurality of holes constituting any one of the one-dimensional hole, the two-dimensional hole, and the three-dimensional hole to each other.
7. The functional structure according to any one of claims 1 to 6, wherein the framework is a carrier that supports the functional substance.
8. 8. The functional structure according to claim 1, wherein an average particle size of the functional substance is equal to or smaller than an inner diameter of the expanded portion.
9. The functional structure according to any one of claims 1 to 8, wherein the metal element (M) of the functional substance is contained in an amount of 0.5 to 2.5 mass % relative to the functional structure.
10. the average inner diameter of the passageways is between 0.1 nm and 1.5 nm; 10. The functional structure according to claim 1, wherein the inner diameter of the expanded portion is 0.5 nm to 50 nm.
11. 11. The functional structure according to claim 1, further comprising at least one functional material carried on the outer surface of the framework, the functional material being a catalytic material.
12. 12. The functional structure according to claim 11, wherein the content of the at least one functional substance present inside the framework is greater than the content of the at least one functional substance held on the outer surface of the framework.
13. The functional structure according to any one of claims 1 to 12, wherein the zeolite type compound is a silicate compound.
Citation Information
Patent Citations
Production of metal-zeolite catalyst
JP1984132940A
Ceramic catalyst body
US20030109383A1
Hydroprocessing catalyst and hydroprocessing catalyst of making the same
US20160030934A1
Process for the preparation of hybrid zeolite or zeolite-like materials
WO2010097108A1
Use of hollow zeolites doped with bimetallic or trimetallic particles for hydrocarbon reforming reactions
WO2017072698A1